Acute Unilateral Vestibular Failure Does Not Cause Spatial Hemineglect. - Julian Conrad; Maximilian Habs; Thomas Brandt; Marianne Dieterich (PLoS ONE, 2015)
Visuo-spatial neglect and vestibular disorders have common clinical findings and involve the same cortical areas. We questioned (1) whether visuo-spatial hemineglect is not only a disorder of spatial attention but may also reflect a disorder of higher cortical vestibular function and (2) whether a vestibular tone imbalance due to an acute peripheral dysfunction can also cause symptoms of neglect or extinction. Therefore, patients with an acute unilateral peripheral vestibular failure (VF) were tested for symptoms of hemineglect.Twenty-eight patients with acute VF were assessed for signs of vestibular deficits and spatial neglect using clinical measures and various common standardized paper-pencil tests. Neglect severity was evaluated further with the Center of Cancellation method. Pathological neglect test scores were correlated with the degree of vestibular dysfunction determined by the subjective visual vertical and caloric testing.Three patients showed isolated pathological scores in one or the other neglect test, either ipsilesionally or contralesionally to the VF. None of the patients fulfilled the diagnostic criteria of spatial hemineglect or extinction.A vestibular tone imbalance due to unilateral failure of the vestibular endorgan does not cause spatial hemineglect, but evidence indicates it causes mild attentional deficits in both visual hemifields.